Police Crackdowns, Human Rights Abuses, and Sex Work Industry in Nigeria: Evidence From an Empirical Investigation - Fawole, Olufemi Adeniyi (International criminal justice review, 2021)
This study undertook a qualitative investigation into police crackdowns as a form of operational control mechanism employed to suppress sex workers and sex work industry in Ilorin Emirate, Kwara State, Nigeria. The study employed a qualitative research method. One hundred and six female commercial sex workers (41 at street hot spots and 65 in brothels) participated. They were aged between 19 and 47 and selected through a variety of sampling methods including purposive, referral, and venue-based sampling methods. In-depth interview was the instrument used in data collection, and thematic data analysis was employed in analyzing the data. Results indicate that police crackdown is usually experienced by sex workers at street hot spots and in brothels and are often associated with brutality, human rights abuses, and extortion, which have negative impacts on the livelihoods and general well-being of sex workers. Sex workers devised some strategies to escape and avoid police arrests and abuses. Thus, crackdowns merely displace sex workers during intense restrictions but do not reduce sex work activities. Therefore, the study suggests a change in suppressive approach to an inclusive nonviolent method in reducing commercial sex work activities.